Scutellaria incarnata Vent. root extract and isolated phenylethanoid glycosides are neuroprotective against C2-ceramide toxicity. (10th May 2023) - Vásquez-Londoño, Carlos A.; Howes, Melanie-Jayne R.; Costa, Geison M.; Arboleda, Gonzalo; Rojas-Cardozo, Maritza A.
Abstract: Ethnopharmacological relevance: Neuronal death is a central process in neurodegenerative diseases and represents a therapeutic challenge for their prevention and treatment. Scutellaria incarnata Vent. roots are used traditionally in Colombia for central nervous system conditions including those affecting cognitive functions, but their chemistry and neuroprotective action remain to be explored to understand the scientific basis for their medicinal uses. In this study, S. incarnata roots are investigated to assess whether they have neuroprotective effects that could provide some explanation for their traditional use in neurodegenerative diseases. Aim of the study: To evaluate the neuroprotective effect of S. incarnata roots and its chemical constituents against C2 -ceramide-induced cell death in Cath.-a-differentiated (CAD) cells. Materials and methods: S. incarnata root ethanol extract was fractionated and compounds were isolated by column chromatography; their structures were elucidated by nuclear magnetic resonance spectroscopy, mass spectrometry and infrared spectroscopy. The cytotoxic and neuroprotective effects against C2 -ceramide of S. incarnata root extract, fractions and isolated compounds were assessed in CAD cells. Results: S. incarnata root extract and its n -butanol fraction were not cytotoxic but showed neuroprotective effects against C2 -ceramide toxicity in CAD cells. The phenylethanoid glycosides incarnatoside (isolated for the first time) and stachysoside C (12.5, 25 and 50 μg/mL) from S. incarnata roots also protected CAD cells against C2 -ceramide without inducing cytotoxic effects. Conclusion: The observed neuroprotective effects of S. incarnata root extract and isolated phenylethanoid glycosides in CAD cells provide an ethnopharmacological basis for the traditional use of this species in Colombia for central nervous system disorders. Graphical abstract: Image 1 Highlights: The neuroprotective effect of S. incarnata root extract provides an ethnopharmacological explanation for its traditional use. The bioactive stachysoside C and a new compound, incarnatoside, are reported for the first time in the genus Scutellaria. Neuroprotective phenylethanoid glycosides from S. incarnata root provides new understanding of its bioactive constituents.